Formulating IP strategies for service-intense business models: A roadmapping-based approach. (September 2022) - Blümel, Jan H.; Tietze, Frank; Phaal, Rob
Abstract: The increasing adaptation of product-service systems (PSS) creates unmet challenges for intellectual property (IP) management and requires an approach to formulate specialised IP strategies for service-intense business models. Building on a roadmapping-based approach for IP strategy formulation we propose a specialised process and template that was developed and demonstrated in one in-depth qualitative case study with a UK-based high-tech scale-up SME. The study shows how the six-step process and template can be applied for the formulation of an IP strategy for a service-intense company. The research demonstrates that a distinct consideration of the PSS components, namely service, product and infrastructure is needed when formulating IP strategies as these different components are likely related to different types of IP rights. This increases the comprehensibility of the IP strategy and provides guidelines for practical implementations.